Broken people : a novel - Lansky, Sam (Hanover Square Press, 2020)
"This is what hooks Sam when he first overhears it at a fancy dinner party in the Hollywood hills: the story of a globe-trotting shaman who claims to perform 'open-soul surgery' on emotionally damaged people. For neurotic, depressed Sam, new to Los Angeles after his life in New York imploded, the possibility of total transformation is utterly tantalizing. He's desperate for something to believe in, and the shaman - who promises ancient rituals, plant medicine, and encounters with the divine--seems convincing enough for Sam to sign up for a weekend under his care."--Publisher.